Studi Komparasi Keanekaragaman Serangga di Kebun Kelapa Sawit pada Topografi Tinggi dan Rendahan - Santoso, Hadi; Santi, Idum Satia; Tarmadja, Samsuri (AGROISTA : Jurnal Agroteknologi, 2023)
Environmental conditions can affect insect diversity. Different plantation conditions give rise to changes in the composition of insects. The study aims to determine the diversity of insects in high and low topography. The research was conducted at PT. Djuandasawit Lestari, Muara Tawas Estate located in Musi Rawas, South Sumatra, from December 2022 to March 2023.  The study used purposive sampling methods that are descriptive and exploratory. The study used 2 plantation blocks R58 and Q59), each block has a high and low topographic area. Each block made 10 observation plots with a size of 5 x 5 meters spread in five plots for low and high areas by taking into account the diversity of vegetation. Each research plot was installed with 4 traps, namely pan trap, pitfall trap, sticky trap and sweep net for 10 days of observation. The insects were identified their classification, and diversity index calculated by the Shannon-Wienner and Simpson dominance. The results showed that the abundance of insects in low-level topography was more than in high-altitude topography. A total of 708 individuals were found spread across 12 orders and 27 families in low topography, while in high topography only 537 individuals were found spread across 12 orders and 26 families. The index of insect dominance in lowly and high areas is low. The insects found are mostly predatory insects.